Understanding customer perceptions of internet banking: the case of the UK. Issue 5 (14th September 2015) - Shanmugam, Mohana; Wang, Yen-Yao; Bugshan, Hatem; Hajli, Nick
Abstract : Purpose: – Existing work on internet banking has provided substantial knowledge of the benefits and economic impacts of internet banking from the bank's perspective. However, internet banking provides advantages for customers as well as the banking industry. The purpose of this paper is to investigate customer perceptions of internet banking in the UK with the goal of providing a comprehensive understanding of British internet banking. Design/methodology/approach: – In order to provide the detailed understanding of customers' perceptions of internet banking, a qualitative study was conducted. The primary method of data collection were 25 interviews. To provide triangulation and increase reliability, various documents and secondary data analyses about internet banking in the UK were also used to supplement the analysis. Findings: – The results indicate that money transfers and bill payment are the most popular facilities with UK internet banking adopters. More importantly, security is the most important factor affecting the rate of internet banking adoption in the UK. To resolve customers' security concerns about internet banking, some banks have introduced technologies such as card readers to avoid online fraud. In addition, the authors also found that customers are highly satisfied with internet banking. Research limitations/implications: – The qualitative nature of the study meant that in-depth interviews with a relatively small sample were the most appropriate method to address the research question. Future studies with larger, more representative sample sizes are encouraged to investigate how the findings can be generalized to larger populations. In addition, due to the popularity of social media, future studies are also advised to examine how they can influence customers' perceptions of internet banking and boost its adoption rate. Originality/value: – This paper investigates current perceptions of internet banking in the UK from the customers' perspective. Therefore, the findings of this study complement with existing work that focusses more on the bank's perspective to present a comprehensive understanding of this topic.